PENERAPAN MODEL TEAMS GAMES TOURNAMENT PADA SOAL CERITA MATERI KELILING BANGUN DATAR UNTUK MENINGKATKAN KEAKTIFAN DALAM BERKELOMPOK DI KELAS V SD NEGERI WONOTULUS - Eka Rahmawati; Rintis Rizkia Pangestika; Arum Ratnaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: 1) Describe the application of the Teams Games Tournament model on story problems on the material of the perimeter of flat shapes that will increase group activity in fifth-grade students of Wonotulus State Elementary School. 2) Increase group activity in fifth-grade students at Wonotulus State Elementary School by implementing the Teams Games Tournament model. This study is a Classroom Action Research (CAR) which is carried out in two cycles, each cycle consisting of planning, action implementation, observation, and reflection stages. The research subjects are fifth-grade students of Wonotulus State Elementary School in the 2025/2026 academic year with a total of 13 students. Data collection techniques and instruments used include interviews, observations, tests, and documentation. The results of the study show that 1) the implementation of learning in cycle I obtained a percentage of 69.99% with a good category, increasing in cycle II obtained a percentage of 88.56% with a very good category. 2) Student group activity in Cycle I was 25.87%, categorized as very poor, and in Cycle II, it was 88.13%, categorized as very good. Therefore, the implementation of the Teams Games Tournament model can improve student group activity in story problems on the perimeter of plane figures in fifth grade at Wonotulus Elementary School.